Advanced in vitro Research Models to Study the Role of Endothelial Cells in Solid Organ Transplantation - Peelen, Daphne M.; Hoogduijn, Martin J.; Hesselink, Dennis A.; Baan, Carla C. (Frontiers in Immunology, 2021)
The endothelium plays a key role in acute and chronic rejection of solid organ transplants. During both processes the endothelium is damaged often with major consequences for organ function. Also, endothelial cells (EC) have antigen-presenting properties and can in this manner initiate and enhance alloreactive immune responses. For decades knowledge about these roles of EC have been obtained by studying both in vitro and in vivo models. These experimental models poorly imitate the immune response in patients and might explain why the discovery and development of agents that control EC responses is hampered. In recent years, various innovative human 3D in vitro models mimicking in vivo organ structure and function have been developed. These models will extend the knowledge about the diverse roles of EC in allograft rejection and will hopefully lead to discoveries of new targets that are involved in the interactions between the donor organ EC and the recipient’s immune system. Moreover, these models can be used to gain a better insight in the mode of action of the currently prescribed immunosuppression and will enhance the development of novel therapeutics aiming to reduce allograft rejection and prolong graft survival.